Nanomedicine applications in women's health: state of the art - Lloyd-Parry, O; Downing, C; Aleisaei, E; Jones, C; Coward, K (Dove Press, 2018)
State-of-the-art applications of nanomedicine have the potential to revolutionize the diagnosis, prevention, and treatment of a range of conditions and diseases affecting women’s health. In this review, we provide a synopsis of potential applications of nanomedicine in some of the most dominant fields of women’s health: mental health, sexual health, reproductive medicine, oncology, menopause-related conditions and dementia. We explore published studies arising from in vitro and in vivo experiments, and clinical trials where available, to reveal novel and highly promising therapeutic applications of nanomedicine in these fields. For the first time, we summarize the growing body of evidence relating to the use of nanomaterials as experimental tools for the detection, prevention, and treatment of significant diseases and conditions across the life course of a cisgender woman, from puberty to menopause; revealing the far-reaching and desirable theoretical impact of nanomedicine across different medical disciplines. We also present an overview of potential concerns regarding the therapeutic applications of nanomedicine and the factors currently restricting the growth of applied nanomedicine.